KETERAMPILAN MEMBERIKAN PERHATIAN DALAM KONSELING DAN TELAAH AYAT ALQURAN - Thalib, Thalib (Hunafa: Jurnal Studia Islamika, 2008)
The purpose of this study was to investigate attending skill in counseling and quranic verses. This study was conducted employing descriptive-qualitative method. The data were collected from written sources and quarnic verses through five phases (1) analyzing theory, (2) collecting apparopriate quranic verses, (3) classifying relevant quranic  verses, (4) doing discussion; and (5) drawing conslusion. The results of this study indicated that from 27 quranic verses studied, there were six verses relevant to the concept of attending skill in counseling; two  verses relevant enough; seven verses lack of relevance; and twelve verses irrelevant.Kata Kunci:  attendind skill, konseling, ayat  Alquran